Challenges in Sustaining Halal Product Assurance among MSMEs in Aceh: Implications for the Islamic Economic Ecosystem - Jalilah Jalilah; Muhibbuthabry Muhibbuthabry; Analiansyah Analiansyah (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2026)
Objective: This study investigates the challenges of sustaining halal product assurance among Micro, Small, and Medium Enterprises (MSMEs) in Aceh following halal certification and examines their implications for the Islamic economic ecosystem. Method: A socio-legal approach integrated with a normative-empirical method was employed through regulatory analysis, in-depth interviews, and field observations. Data were collected from halal-certified MSMEs and relevant stakeholders, including the BPJPH Supervision Directorate, LPPOM MPU Aceh, and LP3HI UIN Ar-Raniry. The data were analyzed using Braun and Clarke's (2006) six-phase thematic analysis. Result: The findings reveal significant gaps between the requirements of the Halal Product Assurance System (SJPH) and MSME practices in five post-certification dimensions: internal audits, halal documentation, the role of Halal Supervisors, raw material monitoring, and self-declaration. SJPH implementation remains largely administrative rather than substantive. The study also identifies the Aceh Paradox, whereby strong religiosity and Sharia-based governance inadvertently foster a taken-for-granted attitude that weakens adherence to formal post-certification requirements. Implication: Sustainable halal assurance requires consistent SJPH implementation, strengthened Halal Supervisor capacity, post-certification mentoring, and institutional synergy. This study contributes to the literature by introducing the Aceh Paradox as a contextual explanation for post-certification discipline challenges among halal-certified MSMEs. Originality/Novelty: This study contributes to the halal assurance literature by introducing the concept of the Aceh Paradox. This contextual empirical finding explains how strong religious commitment and comprehensive Sharia governance structures may unintentionally undermine formal post-certification discipline among halal-certified MSMEs.